MANAJEMEN KINERJA PEGAWAI SEBAGAI STRATEGI MENINGKATKAN PROFITABILITAS - Maradiana, Chantika (JRPA - Journal of Regional Public Administration, 2025)
This research aims to examine the role of employee performance management in improving organizational profitability through a literature study approach. Various studies in Indonesia during 2019-2024 showed that factors such as work motivation, leadership, organizational climate, work culture, and work discipline significantly affect employee performance. Low motivation and job satisfaction, weak organizational culture, and less innovative leadership are the main obstacles in performance management. To overcome these obstacles, strategies such as providing incentives, developing leadership, and improving the performance appraisal system are needed. The results show that employee performance management directly contributes to increased profitability through increased productivity, employee engagement, and effective management of intellectual capital. Investment in training, implementation of measurable KPIs, and a supportive work environment are proven to drive optimal performance. In addition, transformational leadership style and spirituality-based organizational culture also play an important role in shaping employee loyalty and commitment to the organization. Thus, performance management strategies that include competency development, fair compensation, adaptive leadership, and the creation of a positive work environment are very important to implement. The implementation of these strategies not only improves individual performance, but also positively impacts the profitability of the organization as a whole.